Next-Generation Cancer Treatment: Photoimmunotherapy’s Promise for Unresectable Head and Neck Cancers - Laura Marinela Ailioaie; Constantin Ailioaie; Gerhard Litscher (Pharmaceutics)
Traditional oncological therapies have contributed to reducing the global cancer burden; however, they have not achieved complete eradication, nor have they effectively prevented relapses, minimized toxicity, or preserved immune function. Recent advances, particularly the introduction of immune checkpoint inhibitors (ICIs) and CAR-T cell therapies, have markedly improved clinical outcomes and overall survival in certain cancer subtypes. Nevertheless, response rates remain suboptimal, and adverse immunological events are frequent. This review starts by highlighting the FDA-approved ICIs currently utilized in cancer immunotherapy, emphasizing those that have demonstrated clinical efficacy in recent years. The true focus of our analysis is on the latest clinical applications of near-infrared photoimmunotherapy (NIR-PIT). This emerging modality is evaluated in patients with head and neck cancers (HNC), particularly in cases that are unresectable, locally advanced, or recurrent. Finally, the review explores the current landscape and prospects of NIR-PIT, considering its potential to enhance therapeutic efficacy and extend relapse-free survival. Photoimmunotherapy is a promising, molecularly targeted option for patients with limited prognosis, offering new hope where conventional therapies fail. By synthesizing recent clinical trial data, this work highlights how NIR-PIT could bridge the translational gap between preclinical research and clinical practice. The integration of advanced technologies and interdisciplinary collaboration among researchers, clinicians, and technologists will be critical in optimizing NIR-PIT, improving its accuracy, efficacy, and safety, and ultimately advancing standards of cancer care and patient survival.